2022
DOI: 10.1111/jog.15498
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis‐related spontaneous hemoperitoneum in pregnancy: A case series

Abstract: Endometriosis can be associated with adverse pregnancy outcomes. We report six cases of endometriosisrelated spontaneous hemoperitoneum diagnosed in pregnant and postpartum women over 13 years. Spontaneous hemoperitoneum in pregnancy mainly occurred in the second half of gestation. All women presented with acute abdominal pain; four of them needed an emergent surgery, two were managed expectantly. The median estimated blood loss was 4250 ml, four women required massive transfusion. Three out of six women had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…In conclusion, our case highlights a rare but potentially catastrophic clinical presentation in pregnancy 1 7–9. SHiP has been associated with a number of causes including endometriosis 5.…”
Section: Discussionmentioning
confidence: 68%
“…In conclusion, our case highlights a rare but potentially catastrophic clinical presentation in pregnancy 1 7–9. SHiP has been associated with a number of causes including endometriosis 5.…”
Section: Discussionmentioning
confidence: 68%
“…An advantage of CT is the ability to determine the most likely origin of the haemorrhage. The fetal exposure to radiation during CT is estimated at 9 mGy, which is below the advised maximum allowed dose for fetuses 33,38 …”
Section: Discussionmentioning
confidence: 95%
“…The fetal exposure to radiation during CT is estimated at 9 mGy, which is below the advised maximum allowed dose for fetuses. 33,38 This was the first study on nationwide obstetric complications that used an online DAS. Overall, the audit panel was satisfied with the use of the DAS.…”
Section: Physical Examinationmentioning
confidence: 99%
“…A large multicentre prospective cohort study 8 completed in Italy reported an incidence of 0.04/1000 births. Bazurini et al 1 reported a case series of six patients over 13 years with an estimated prevalence of 1.7/10,000 births. This literature review highlights the limited available evidence on this topic and the need for further research to enhance our understanding of the underlying mechanisms, risk factors and optimal management strategies.…”
Section: Incidencementioning
confidence: 99%
“…Spontaneous haemoperitoneum is uncommon during pregnancy, and its association with endometriosis further adds to the complexity of the condition. 1 , 2 SHiP is spontaneous, non-traumatic intraperitoneal bleeding in pregnancy and up to 42 days after delivery requiring surgical intervention or embolisation, not due to uterine rupture, ruptured ectopic pregnancies, or caesarean section-related bleeding. 2 , 3 SHiP has been described in the setting of ruptured uterine arteries, varicose veins or aneurysms of the splenic artery, but causes due to endometriosis are increasingly reported in the literature.…”
Section: Introductionmentioning
confidence: 99%